Project-based Learning (PjBL) based on the Digital Module to Improve Conceptual Understanding in Aviation English - Fitri Masito; Sudarwan Danim; Sapriyadin Sapriyadin; Eko Risdianto; Christina Brown (Journal of Innovation in Educational and Cultural Research, 2023)
This research is triggered by the lack of students’ conceptual understanding of Aviation English. A digital module assists in delivering engaging lessons. This research aims to examine the effectiveness of the Project-based Learning (PjBL) model based on the Digital Module to improve students’ conceptual understanding of Aviation English. This research applied the research and development (RD) model proposed by Borg and Gall (1982). The method was modified into three research and development steps, including (1) preliminary study, (2) development, and (3) evaluation. The research was conducted at Politeknik Penerbangan Palembang. The research subjects were 47 students of the Aviation Rescue and Firefighting Department. The data collection method used a questionnaire and test. Based on the data analysis, most students strongly agreed to use the digital module to improve students’ conceptual understanding of Aviation English. The use of the PjBL model based on the digital module affects significantly students’ conceptual understanding of Aviation English. This is demonstrated by the average scores of post-test results for the control and experimental classes are 70.57 and 80.03 respectively.